Core elements in the process of citing publications: Conceptual overview of the literature - Tahamtan, Iman; Bornmann, Lutz (Journal of informetrics, 2018)
[Display omitted] •We provide a conceptual overview of the literature on the process of citing publications.•The overview presents the results of studies having theoretically or empirically analyzed this process.•The overview is referred to as conceptual, because it is structured based on core elements in the citation process.•The conceptual overview can be used to find answers on basic questions about the practice of citing documents.•The overview delivers basic information for the proper application of citations in research evaluation. This study provides a conceptual overview of the literature dealing with the process of citing documents (focusing on the literature from the recent decade). It presents theories, which have been proposed for explaining the citation process, and studies having empirically analyzed this process. The overview is referred to as conceptual, because it is structured based on core elements in the citation process: the context of the cited document, processes from selection to citation of documents, and the context of the citing document. The core elements are presented in a schematic representation. The overview can be used to find answers on basic questions about the practice of citing documents. Besides understanding of the process of citing, it delivers basic information for the proper application of citations in research evaluation.